Perspektif pembelajaran Bahasa Mandarin mahasiswa program 3+1 di Guangxi Normal Universitydan Universitas Negeri Malang - Dwiyanti, Faradilla Rizky (2020)
Language and culture are closely related to human life. As the times progress, the culture of other countries can be learned easily. In addition to being able to study culture in our own country, we can also learn culture and language in various ways, one of which participates in scholarship programs and student exchanges provided by their respective universities. With the cooperation between Malang State University and Guangxi Normal University resulted in a student exchange program named after the 3+1 program. It is very effective for learning Chinese language and its culture. With this problem, we do reasearch how to learn Mandarin in China and Indonesia according to students of the 3+1 program of Malang State University